b c ( b + c ) 2 + c a ( c + a ) 2 + a b ( a + b ) 2
If a + b + c = 0 , what is the value of the expression above?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Please explain why a 3 + b 3 + c 3 = 3 a b c . Did I miss something?
Log in to reply
we have,
(
a
+
b
+
c
)
3
=
a
3
+
b
3
+
c
3
+
3
a
2
b
+
3
a
2
c
+
3
b
2
c
+
3
b
2
a
+
3
c
2
a
+
3
c
2
a
+
6
a
b
c
.
Since a + b + c = 0, it must be that
0
=
a
3
+
b
3
+
c
3
−
3
a
3
−
3
b
3
−
3
c
3
+
6
a
b
c
,
which gives
a
3
+
b
3
+
c
3
=
3
a
b
c
.
Given
a+b+c=0---->(1)
From (1)
b+c=-a
c+a=-b
a+b=-c
Now
b c ( b + c ) 2 + c a ( c + a ) 2 + a b ( a + b ) 2
⇒ b c ( a ) 2 + c a ( b ) 2 + c a ( c ) 2
⇒ ( a b c ) 2 a 4 b c + b 4 c a + c 4 a b
⇒ abc( ( a b c ) 2 a 3 + b 3 + c 3 )
⇒ a b c a 3 + b 3 + c 3 ---->(2)
When a + b + c=0 then a 3 + b 3 + c 3 =3abc
By substituting a 3 + b 3 + c 3 =3abc in (2), we get
a b c 3 a b c =3
Therefore b c ( b + c ) 2 + c a ( c + a ) 2 + a b ( a + b ) 2 when a + b + c = 3
Problem Loading...
Note Loading...
Set Loading...
b c ( b + c ) 2 + c a ( c + a ) 2 + a b ( a + b ) 2 = b c a 2 + c a b 2 + a b c 2 = a b c a 3 + b 3 + c 3 = a b c 3 a b c = 3 ( Because if a + b + c = 0 , then a 3 + b 3 + c 3 = 3 a b c )